PENGGUNAAN RUMPUT LAUT LAUT (Sargassum polycystum) SEBAGAI BAHAN PUPUK CAIR DAN PENGARUHNYA TERHADAP KANDUNGAN N,P,K,Ca,Mg TANAH ULTISOL DANPRODUKSI SAWI ( Brassica juncea L. ) ORGANIK - Ricky Ricky Ambarita; Alida Lubis; Hardy Guchi, (Universitas Sumatera Utara, 2014)
This study aims to find out the use of seaweed ( Sargassum polycystum ) as a liquidfertilizer and its effect on N , P , K , Ca , Mg Ultisol and mustard (Brassica juncea L. )growth organically. The study was carried out in the Screen House and Laboratory ofChemical and Soil Fertility , and Central Laboratory , Faculty of Agriculture ,University of North Sumatra , Medan since January until March 2012. This researchused Randomized Block Design( RBD ) non factorial of nine treatments with tworeplication so there are two eighteen experimental unit . The treatment consists of P0(control) , P1 (application of liquid seaweed fertilizer A-type every two days) , P2(application of liquid seaweed fertilizer A-type every three days ), P3(application ofliquid seaweed fertilizer A-type every four days), P4 (application of liquid seaweedfertilizer A- type every five days), P5 (application of liquid seaweed fertilizer B-typeevery two days), P6 (aplication of liquid seaweed fertilizer B-type every three days ), P7( application of liquid seaweed fertilizer B-type every four days ) , P8 (application ofliquid seaweed fertilizer B-type every five days ). A-type of fertilizer use EM-4 20 ccand B-type use EM-4 40 cc. The results showed that application of liquid seaweedfertilizer did not differ significantly affected soil total P, available P, soil total K , Kexchangeable,Ca-exchangeable, Mg- exchangeable and plant dry weight. Butsignificantly different on the soil N, plant height, leaf area, number of Leaf, chlorophyllcontent, plant mass weight, plant fresh weight for market. The highest weight of plantmasss achieve on the treatment P4 that is weighing 149.1 g.Keywords: polyscystum sargassum, seaweed fertilizer, mustard (Brassica juncea L)